APPLICATION OF WAVELET ANALYSIS AND FOURIER TRANSFORM METHODS IN PROBLEMS OF OBJECT DIAGNOSTICS BY VIBROACOUSTIC SIGNAL - Afonin, Y. S.; Dubrovin, V. I.; Manilo, T. V. (Radio Electronics, Computer Science, Control, 2024)
The methods of wavelet analysis (fast and packet wavelet transform) and Fourier-transform for vibroacoustic signal processing in the context of their application for the task of object diagnostics are presented. The characteristics (results of vibroacoustic signals processing), related to the object state under consideration are revealed for each method. The methods comparison by signal processing time is performed.